Bermuda : aberrant or exemplary case - CONNELL, John (1997)
Examines why the majority of people in Bermuda have chosen to consolidate their dependence on colonial rule, and on the global economy, rather than choosing independence, and notes that this choice seems to fly in the face of contemporary change. Discusses the relationship between political independence, economic development and national identity.